BIOPHYSICAL FOUNDATIONS OF LASER TECHNOLOGIES IN INCREASING AGRICULTURAL PRODUCTIVITY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article theoretically analyzes the biophysical foundations of using laser technologies to increase agricultural productivity. The effects of laser radiation on plant seeds and tissues, its mechanisms at the cellular level, its role in activating biochemical processes, and the prospects of its application under the agro-climatic conditions of Surkhandarya region are considered. Pre-sowing stimulation of seeds using low-intensity laser radiation is substantiated as an effective method for increasing seed germination energy, plant growth rate, and resistance to stress factors.